The effect of bowing technique on violin sound - Jálics, Károly; Jálics, Sr, Károly (Design of Machines and Structures, 2024)
By the bowing of a violin especially by folk and gipsy bands a special bowing technique can be observed. Often a diagonal (not perpendicular to the string) bowing, resp. the bow slids onto the fingerboard. This study deals with the effect of this special bowing technique on the emitted sound of a violin and compares it with the classic detaché bowing technique on all four strings.